2018
DOI: 10.1038/s41598-018-28461-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between hydrogen and gallium vacancies in β-Ga2O3

Abstract: In this paper, the revised Heyd-Scuseria-Ernzerhof screened hybrid functional (HSE06) is used to investigate the interaction between hydrogen with different concentrations and gallium vacancies in β-Ga2O3. The hydrogen can compensate a gallium vacancy by forming hydrogen-vacancy complex. A gallium vacancy can bind up to four hydrogen atoms, and formation energies decrease as the number of hydrogen atoms increases. Hydrogen prefers to bind with three coordinated oxygen. The bonding energy and annealing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
(42 reference statements)
2
19
0
1
Order By: Relevance
“…[35][36][37][38][39] Hydrogen-gallium vacancy complexes (i.e., V Ga -H, V Ga -2H) might also play a role since irradiation can affect the degree of H saturation of V Ga with different charge state transitions, (0/−1), (−1/−2), (−2/−3), etc., which has also been reported for proton-implanted β-Ga 2 O 3 with the V Ga -2H complex formation, 44 and possibly cause Frenkel pair generation. 39,45 Regarding the E C −4.48 eV state that remained unaffected after irradiation for both doses, this energy level is close to those that have been predicted for vacancies; 38,46 however, Note that the concentrations of the DLOS traps before and after irradiation are likely even greater (but at same ratio) than shown here due to their small optical cross sections causing an underestimation of these values.…”
Section: Article Scitationorg/journal/apmsupporting
confidence: 86%
“…[35][36][37][38][39] Hydrogen-gallium vacancy complexes (i.e., V Ga -H, V Ga -2H) might also play a role since irradiation can affect the degree of H saturation of V Ga with different charge state transitions, (0/−1), (−1/−2), (−2/−3), etc., which has also been reported for proton-implanted β-Ga 2 O 3 with the V Ga -2H complex formation, 44 and possibly cause Frenkel pair generation. 39,45 Regarding the E C −4.48 eV state that remained unaffected after irradiation for both doses, this energy level is close to those that have been predicted for vacancies; 38,46 however, Note that the concentrations of the DLOS traps before and after irradiation are likely even greater (but at same ratio) than shown here due to their small optical cross sections causing an underestimation of these values.…”
Section: Article Scitationorg/journal/apmsupporting
confidence: 86%
“…6) and the H  formation was accelerated by DCP. Conductivity of Ga-or In-based alloys is dependent on the extent of Hdoping 28,35,36 . Since H  generation is proportional to the fraction of ethylene (E) in PEVA, the conductivity increased as E (red line in Fig.…”
mentioning
confidence: 99%
“…They support these conclusions by using density functional theory (DFT) to calculate the binding energies of one, two, three, and four H atoms at the Ga(1) vacancy. These processes, if supported by subsequent results, could play significant roles in the understanding 2 and applications 3,4 of b-Ga 2 O 3 , as noted by Polyakov et al 5 However, the models of these defects and of the Ga(1) vacancy suggested by Islam et al 1 and earlier by Wei et al 6 involve an unshifted configuration of this defect and have not taken account of the remarkable spontaneous restructuring of the Ga(1) defect that has been found to take place, both with and without trapped H. Specifically, the Ga(1) vacancy is metastable against lower-energy shifts into two inequivalent configurations (Fig. 1) in which a neighboring Ga(1) moves to an interstitial position halfway between its original site and the site of the vacancy.…”
mentioning
confidence: 60%
“…However, we find that each of these three-and four-H unshifted-vacancy configurations would have at least one vibrational mode with a strong [010] component, and there is no experimental evidence [15][16][17] for such modes. Thus, the absence of any defects with H atoms trapped at an unshifted Ga(1) vacancy with the structures proposed by Islam et al 1 or Wei et al 6 in spite of their low energy appears to be a puzzle.…”
mentioning
confidence: 87%
See 1 more Smart Citation